Virtual Reference Services: Connecting Users with Experts and Supporting the Development of Skills - Bakker, Trix (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
Virtual reference - a service that allows librarians and patrons to communicate with each other in real time through the Internet by e-mail, chat or instant messaging - is currently a hot topic in libraries. In a way the commercial sector has challenged the reference function by offering Question & Answer services. To librarians this represents a threat and an opportunity. They can benefit from technologies and service models developed for the commercial arena by adapting these to virtual reference applications that will more effectively meet the needs of libraries on the Web. The literature provides many examples of pilots and experiments in taking reference into cyberspace. After an introduction to the in-and-outs of virtual reference, follows a short exposition of a virtual tour in the Netherlands where 7 of the 13 university libraries and the Royal Library have a basic ‚virtual helpdesk’. One thing is clear: virtual reference services are definitely put high on the agenda of the Dutch libraries. The Royal Library is one of the Dutch libraries, which is going to participate with QuestionPoint, formerly called Collaborative Digital Reference Service (CDRS), jointly developed by the Library of Congress and OCLC, which will provide web-based reference service to researchers anytime, anywhere, through an international, online network of member libraries.